Market Reaction Towards Dividen Tax Rate Changes of The Omnibus Law on Job Creation In Indonesia - Dedi Purba (Syntax Corporation, 2023)
This paper is to investigate the changes in the dividend tax rate effect on the stock price of the companies listed in Indonesia Stock Exchange (IDX) and to demonstrate the existence of abnormal returns by examining stock trading situations before and after the ex-dividend date. Standard event study methodology, using the market model, is employed to determine the abnormal returns surrounding the ex-dividend date. The findings are useful to researchers, practitioners and investors interested in companies listed on the Indonesian stock market for their proper strategic decision making. In particular, the results can be used to encourage transparency and good governance practices in the Indonesian stock market. This study is the first to use dividend tax rate data after the Introduction of the Omnibus Law on Job Creation and the Law on Harmonization of Tax Regulations. By using the event study method, the study reveals that there is no significant difference in abnormal returns prior to and following the ex-dividend date, both preceding and subsequent to the reduction in the new tax rate. Thus, the dividend tax rate reduction does not affect the market reaction in the event window.